A Mechatronic Shape-Shifting Reflector System With True Independent Reflection Magnitude and Phase Control for Dynamic Beamforming - Keigan Macdonell; Debidas Kundu; Shulabh Gupta (IEEE Access)
A novel shape-shifting mechatronic reflector system is proposed and demonstrated experimentally with a variety of real-time beam-forming examples. The reflector system consists of a 1D array of panels of sub-wavelength split ring resonators (SRR) loaded with PIN diodes for reflection magnitude control and a stepper motor array that de-embeds each panel to achieve column-by-column phase control, thus offering excellent decoupling between magnitude and phase. A complete system prototype is built including a printed circuit board (PCB) based resonator array forming the reflector front end, a stepper motor array assembly, a custom-built chassis using 3D-printed parts, and a fully programmable analog and digital electronic back-end for PIN diode biasing and motor control. The real-time beam-forming feature of the proposed reflector system is further experimentally demonstrated using illustrative examples of single beam steering with gain control and the generation of asymmetric dual beam radiation patterns where the two beams are independently controlled - a capability unlocked through achieving true decoupling between reflection magnitudes and phases.